The impact of the use of digital marketing channels on the implementation of the strategy of positioning Applied study on a sample of the managers of the International Company for smart card "Key Card" - جاسم, سرمد حمزة; عبد الحسين, سماء علي (Journal of Economics and Administrative Sciences, 2020)
The technology in continuous and quick development, that reflects in all parts of our life and interred both scientific and practical fields. Marketing is one of them, a customer’s way to deal with choosing and demanding the product deferent from the traditional way. Some of the buying processes are electronic now, therefore the current research is identifying the digital channels that entered the world of marketing and influenced the activities and types that fall under this name and how it affects in positioning strategy, which is how to install the product or brand in the mind of the customer and was dimensions (brand identity, brand personality, brand communication, brand awareness, brand image), The researcher took the basic problem of the change in the application of marketing operations using digital channels and how it reflected in the application of the steps of positioning, and the aim of the research was employ digital channels in the application of the strategy of positioning and study the relationship between variables and test according to the hypothesis “The digital marketing channels have a significant impact on positioning strategy”, the managers of the global smart card company in Iraq were chosen 203 managers of the research community and 86 of them were selected for a practical sample to test the hypothesis using the statistical methods of The means and standard deviation to measure the homogeneity of the answers on the questions asked and the simple linear regression to measure the degree of influence between the variables tested. The research found that there is a relationship of influence of digital channels in the application of the strategy of concentration, and the stronger impact on the identity of the brand while the character of the mark relationship weaker, and the researcher recommended to focus on strengthening the elements of the identity of the mark in promotional messages and also needs to strengthen the brand by adopting the principles of commitment and honesty By providing the customer with more honest information and commitment to the timing of service delivery to complete the subsequent steps and crystallize concentration in the mind of the target customer.